Handbook of bereavement research : consequences, coping, and care - Stroebe, Margaret S.; Hansson, Robert O.; Stroebe, Wolfgang; Schut, Henk (American Psychological Association, 2001)
he Handbook of Bereavement Research provides a broad view of diverse contemporary approaches to bereavement, examining both normal adaptation and complex manifestations of grief. In this volume, leading interdisciplinary scholars focus on 3 important themes in bereavement research: consequences, coping, and care. In exploring the consequences of bereavement, authors examine developmental factors that influence grief both for the individual and the family at different phases of the life cycle. In exploring coping, they describe new empirical studies about how people can and do cope with grief, without professional intervention. Until recently, intervention for the bereaved has not been scientifically guided and has become the subject of challenging differences of opinion and approach. Chapters in the care section of the volume critically examine interventions to date and provide guidance for assessment and more theoretically and empirically guided treatment strategies. The Handbook provides an up-to-date comprehensive review of scientific knowledge about bereavement in an authoritative yet accessible way that will be essential reading for researchers, practitioners, and health care professionals in the 21st century.